Children's experience of sport in Australia. (August 2017) - McPherson, Lynne; Long, Maureen; Nicholson, Matthew; Cameron, Nadine; Atkins, Prue; Morris, Meg E
Australia is known as a 'sporting nation' and sport is central to its cultural identity. Children's participation in leisure activities, including sport, is considered to be of such importance that it is enshrined as an international human right. There is a growing awareness, however, that children's experience of sport is not always positive and that abuse and harm may occur in organised sport. This paper reports on a study designed to explore children's experiences of organised sport, as recounted by young adults between the ages of 18 and 25 years. A mixed methods study design was implemented, which resulted in 107 survey responses and 10 follow-up interviews with young adults. Overwhelmingly, young people reported the lasting developmental benefits of participation in organised sport as children. More than 50% also reported negative experiences, including emotional and physical harm and sexual harassment. The reasons for these apparently contradictory findings are explored. The role of coaches, peers, parents and the wider sporting association ethos are investigated and suggestions made for future research.